Analisis Variasi Lanskap Linguistik di Museum Negeri Provinsi Sumatera Utara sebagai Daya Tarik Wisata Budaya - Siti Aisyah (Yayasan Literasi Sains Indonesia, 2023)
Language has a very important role in tourist destinations, including museum destinations. As a part of the language used in public spaces, the language used at the Museum of North Sumatra as a Cultural Tourism destination is interesting to study in terms of form, function, meaning and value. This research focuses on finding variations in the linguistic landscape found in Museums of North Sumatera and the language function of the linguistic landscape found. The aims of this research is to obtain a description of the use of language variations used in the linguistic landscape of Museums in North Sumatra. This research uses a qualitative descriptive research design. The data in this research are in the form of visual images of information signs explaining historical heritage objects at the Museum of North Sumatera. The data was taken by taking photos in the form of visual images of information explaining historical heritage objects at the Museum of North Sumatera by using a smartphone camera. Two pictures were taken of each sign and the clearer one was chosen from the two pictures. Based on the results, the linguistic landscape variation that is most often found in the Museum of North Sumatera is the bilingualism variation. This is used to anticipate readability by museum visitors who come from foreign tourists. Abstract Language has a very important role in tourist destinations, including museum destinations. As a part of the language used in public spaces, the language used at the Museum of North Sumatra as a Cultural Tourism destination is interesting to study in terms of form, function, meaning and value. This research focuses on finding variations in the linguistic landscape found in Museums of North Sumatera and the language function of the linguistic landscape found. The aims of this research is to obtain a description of the use of language variations used in the linguistic landscape of Museums in North Sumatra. This research uses a qualitative descriptive research design. The data in this research are in the form of visual images of information signs explaining historical heritage objects at the Museum of North Sumatera. The data was taken by taking photos in the form of visual images of information explaining historical heritage objects at the Museum of North Sumatera by using a smartphone camera. Two pictures were taken of each sign and the clearer one was chosen from the two pictures. Based on the results, the linguistic landscape variation that is most often found in the Museum of North Sumatera is the bilingualism variation. This is used to anticipate readability by museum visitors who come from foreign tourists.